OPTIMIZATION OF THE COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) MODEL TO IMPROVE READING COMPREHENSION AND NARRATIVE TEXT WRITING SKILLS IN INDONESIAN LANGUAGE SUBJECTS IN GRADE III STUDENTS OF SD NEGERI 09 LUBUK ALUNG - Erizal Candra Efendi; Juli Yani (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
The ability to understand reading and write narrative texts is an important aspect in learning Indonesian at the elementary school level. However, the results of observations in class III of SD Negeri 09 Lubuk Alung showed that most students still had difficulty in understanding the contents of the text and composing stories coherently. This is due to the learning method which is still conventional and does not involve students actively. The purpose of this study was to improve students' reading comprehension and narrative text writing skills through the application of the Cooperative Integrated Reading and Composition (CIRC) model. This study is a Classroom Action Research (CAR) which was carried out in two cycles. Each cycle consists of the stages of planning, implementing actions, observation, and reflection. The subjects of the study were 10 students of class III of SD Negeri 09 Lubuk Alung. Data collection techniques included observation, written tests, documentation of student work results, and informal interviews. The research instruments included observation sheets, reading comprehension questions, and narrative text assessment rubrics. Applying the CIRC model increased students' reading comprehension from 30% before the cycle to 90% throughout the second cycle, according to the data. Skills in composing narrative texts also rose throughout this time, going from 20% to 80%. It seemed like students were more invested in the learning process because they were more vocal in class discussions, papers, and presentations. Overall, elementary school students' reading and writing abilities have been significantly enhanced by the Cooperative Integrated Reading and Composition (CIRC) approach. Learning environments that are dynamic, engaging, and meaningful can be achieved through the use of collaborative and integrated learning strategies